(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2007)
The existence of pawestren, women’s room in Javanese mosques, is an opportunity to promote gender equality in Muslim society. Pawestren opens women’s access to public space in Muslim society, yet still unequal to men’s. Architecturally, pawestren occupies lower hierarchy than men’s space in the mosque. The difference is also reflected in the local linguistic terms used for both spaces. In fact, pawestren, in both traditional and modern Central-Javanese mosques is considered to be an annex. This inevitably differs the access and control of women’s from men’s to the mosque. This paper aims at criticizing gender-based segregation of space in the mosque, particularly those in Central Java. Pawestren can be either good or bad potential in Islamic society beyond gender equality. This paper is expected to give insight understanding of gender equality through space and furthermore enhance the gender equality itself in religious buildings.